ANALYSIS OF LOCAL GOVERNMENT FINANCIAL REPORTS IN INDONESIA - Fahri Al Pasha; Agus Maulana (MANKEU (JURNAL MANAJEMEN KEUANGAN), 2024)
This study aims to analyze the financial reports of local governments in Indonesia as an important instrument in financial management. Although many local governments have made efforts to improve the quality of financial reports, challenges such as reliance on transfers from the central government and limited human resource capacity remain major issues. Using a qualitative approach, data was collected from literature studies and official financial report documentation. The analysis results indicate that many regions do not meet the established accounting standards, resulting in an opinion of Qualified Opinion (WDP) or even Unqualified Opinion. This study also identifies the importance of transparency and accountability in financial management to enhance public trust. Recommendations for improvement include enhancing human resource capacity, implementing accrual-based accounting, and involving the community in oversight.